Therapeutic Cytokine Inhibition Modulates Activation and Homing Receptors of Peripheral Memory B Cell Subsets in Rheumatoid Arthritis Patients - Mahmood, Zafar; Schmalzing, Marc; Dörner, Thomas; Tony, Hans-Peter; Muhammad, Khalid (Frontiers in Immunology, 2020)
Memory B cells have known to play an important role in the pathogenesis of rheumatoid arthritis (RA). With the emergence of B cell-targeted therapies, the modulation of memory B cells appears to be a key therapeutic target. Human peripheral memory B cells can be distinguished based on the phenotypic expression of CD27 and IgD, characterizing the three major B cell subpopulations: CD27+IgD+ pre-switch, CD27+IgD- post-switch, and CD27-IgD- double-negative memory B cells. We evaluated different memory cell populations for activation markers (CD95 and Ki-67) and chemokine receptors (CXCR3 and 4) expressing B cells in active RA, as well as under IL6-R blockade by tocilizumab (TCZ) and TNF- blockade by adalimumab (ADA). Memory B cells were phenotypically analyzed from RA patients at baseline, week 12, and week 24 under TCZ or ADA treatment, respectively. Using flow cytometry, surface expression of CD95, intracellular Ki-67, and surface expressions of CXCR3 and CXCR4 were determined. Compared with healthy donors (n=40), the phenotypic analysis of RA patients (n=80) demonstrated that all three types of memory B cells were activated in RA patients. Surface and intracellular staining of B cells showed a significantly higher percentage of CD95+ (p<0.0001) and Ki-67+ (p<0.0001) cells, with numerically altered CXCR3+ and CXCR4+ cells in RA. CD95 and Ki-67 expressions were highest in post-switch memory B cells, whereas CD19+CXCR3+ and CD19+CXCR4+ expressing cells were substantially higher in the pre-switch compartment. In all subsets of the memory B cells, in vivo IL-6R and TNF- blockade significantly reduced the enhanced expressions of CD95 and Ki-67. Based on our findings, we conclude that the three major peripheral memory B cell populations, pre-, post-switch, and double-negative B cells, are activated in RA, demonstrating enhanced CD95 and Ki-67 expressions, and varied expression of CXCR3 and CXCR4 chemokine receptors when compared with healthy individuals. This activation can be efficaciously modulated under cytokine inhibition in vivo.